"Faszyści z SiN-u" = "Fascists of SiN" - Bereś, Stanisław (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The fate of the legendary "Art and the Nation" (SiN) underground periodical published in Warsaw from April 1942 to July 1944 (16 issues) by the National Confederation (KN), a far-right organization, deserves to be described in a major work, and not in a 30-page summary. Some of the most talented poets from the Columbus generation had their works published there, among others Wacław Bojarski, Lesław M. Bartelski, Tadeusz Gajcy, Stanisław Marczak, Tadeusz Sołtan, Zdzisław Stroiński, Andrzej Trzebiński. All of its young editors were killed by Germans, and after the war, for political reasons, their poems, drammas and sketches blocked by the communist regime, were slowly returning to the canon of twentieth-century Polish literature for almost half a century, although literary critics have always stressed the importance of their poetry, drama and journalism, and they were worshipped by the readers. This article shows the complex and multi-phase process in which personal dislike and political hatred faced the admiration of the heroism and talent of writers in their twenties, and also explains the cause of these passions, which survived until our century. Most distinguished Polish writers, critics, literary historians and journalists took part in discussions about their attitudes and poetry, which would come back, like a boomerang, almost every decade. One of them was Czesław Miłosz, who knew the poets personally, and who, for the rest of his life, had a poetical and political dispute with their writing. It was one of the fiercest and lengthy disputes in the history of Polish literature, parallel to the discussion about the importance and meaning of the Warsaw Uprising, symbolized, in some way, by the editorial board of SiN. After all, three of its members were killed on the barricades.
Keywords: czasopismo; grupy literackie; literatura polska; pisarze polscy; poeci polscy; Sztuka i Naród (czasopismo); Miłosz, Czesław (1911-2004); periodicals; literary groups; Polish literature; Polish writers; Polish poets